Rainwater harvesting: potential for quality living - Shaari, Nurulhuda; Che Ani, Adi Irfan; Mohd Zain, Muhammad Fauzi; Goh , Sin Fui (2008)
This paper is in support of the solution which has been given due consideration by the government; namely the implementation of rainwater harvesting system. There are many benefits to be derived from rainwater harvesting; not just for users, but also to environment and government. Water is an important element in human life. Our body consists mostly of water. We need water for drinking, cooking, washing, agriculture and to run our industries. We usually take it for granted because of its availability; but when in scarcity it becomes our most precious resource. Even though 70% of our earth is covered with water, 97% of them were the ocean, 2% was glacier and only 1% of this water is fresh. Out of this, 2% is locked in the form of ice and it is only the balance 1% that is being recycling that flow into the lakes and rivers. A United Nation Study published in 1997 indicated that by 2025, the world population will be effected by moderate to severe water shortage. In Malaysia, we are blessed with an ample supply of water because of abundant rains. Normally, we received the rainfall averaging around 2400mm for Peninsular Malaysia, 2360mm for Sabah and 3830mm for Sarawak. However, increasing usage by our industry, agricultural and household users is straining our existing water supply infrastructure. Sandakan was among the early place that did not get enough treated water supply from its water supply authority since 1984. In 1998, the same situation happened in Peninsular of Malaysia. The cost of adding the water supply infrastructures and replacing the ageing systems to avoid this crisis are burdening the government. In order to avoid water crisis as in 1984 and 1998 will not be repeated, a proactive step must be taken to avoid acute water shortage in future.